Self-Determination: The other side of the coin. Reflections on a central but ambiguous term of the German Disability Rights Movement - Rebecca Maskos; Birger Siebert (Disability Studies Quarterly, 2006)
Since its beginning, independent living has been a crucial demand of the German Disability Rights Movement. The call for independent living and the refusal of its opposite, heteronomy, is the focal point of its critique. Disabled people realized that the way in which disabled people are treated in terms of social policy and of personal care is a form of discrimination and not a natural outcome of their "fate". This insight enabled people with disabilities to claim independent living as a form of liberation. This article sheds light on a critical maxim of the German Disability Rights Movement, its merits and shortcomings, and uses the example of labor and employment as a means for examining its significance.
Keywords: German Disability Rights Movement; self-determination; independent living; workers with disabilities; employment and people with disabilities